Design and Synthesis of Perpendicularly Connected Metal Porphyrin–Imide Dyads for Two‐Terminal Wired Single Molecular Diodes. Issue 25 (23rd May 2014) - Handayani, Murni; Gohda, Syun; Tanaka, Daisuke; Ogawa, Takuji
Abstract Four different porphyrin–imide dyads bearing different central metals (zinc or rhodium) and different substituents on the porphyrin macrocycles (tert‐butyl or methoxy) were synthesized for single molecular diode measurements. The molecules were designed to separate the donor component (porphyrin) from the acceptor component (imide) by bonding in a perpendicular arrangement, thus enhancing the rectification properties. UV/Vis absorption spectra and density functional theory calculations showed that the design was successful and that the molecular orbitals of the dyads were the summation of the two components, with minimal interaction between them. The effect of the central metal was found to be significant, with the lowest energy absorption for the zinc dyads being attributed to the mixed state of charge transfer from porphyrin to imide and the Q band, whereas that of the rhodium dyads indicated insignificant charge‐transfer character.